An unusual cause of massive upper gastrointestinal bleeding—gastric mucormycosis - Guddati, Harish (Oxf Med Case Reports, 2019)
Mucormycosis of the gastrointestinal tract is a life threatening infection most commonly seen in patients with severe immunosuppression. A 42-year-old male with history of choriocarcinoma was admitted to the intensive care unit with septic shock. He developed massive hematemesis requiring upper endoscopy which showed multiple deep gastric ulcers. Due to uncontrollable bleeding he underwent an emergent gastrectomy which revealed necrotic ulcers with evidence of angioinvasion in the ulcer bed with mucor organisms. The PCR revealed the mucor to be Mycotypha microspora which is extremely rare. We discuss the challenges involved in the diagnosis and treatment of gastric mucormycosis.